Toxic exposures : contested illnesses and the environmental health movement - Brown, Phil (Columbia University Press, 2007)
The increase in environmentally induced diseases and the loosening of regulation and safety measures have inspired a massive challenge to established ways of looking at health and the environment. Communities with disease clusters, women facing a growing breast cancer incidence rate, and people of color concerned about the asthma epidemic have become critical of biomedical models that emphasize the role of genetic makeup and individual lifestyle practices. Likewise, scientists have lost patience with their colleagues' and government's failure to adequately address environmental health iss.